Structure of 1-(thiophen-2-ylmethyl)-2-(thiophen-2-yl)-1H-benzimidazole - Dege, N; Sekerci, M; Servi, S; Dinçer, M; Demirabas, Ü (Tubitak Scientific & Technological Research Council Turkey, 2006)
The title compound, C16H12N2S2, crystallizes in the monoclinic space group P2(1)/n with Z = 4, a = 8.950 (5) angstrom, b = 9.141 (5) angstrom, c = 17.429 (5) angstrom and beta = 93-638 (5)degrees. The benzimidazole ring is essentially planar. The crystal structure is stabilized by intermolecular C-H center dot center dot center dot N and C-H center dot center dot center dot pi contacts.
Keywords: 2-Substituted Benzimidazoles